Bond behaviour of NSM CFRP-concrete systems: adhesive and CFRP cross-section influences - Cruz, José Ricardo (2016)
Near Surface Mounted (NSM) strengthening technique has been used in a sustainable way for retrofitting existing structures. This technique, which utilizes CFRP laminates inserted in the concrete cover, has been used due to the several advantages when compared with the technique based on the application of these reinforcing materials on the concrete surface (EBR technique). Although several studies have been developed on this topic in the recent past, open issues still deserve research, such as the influence of the adhesive type on the performance of the NSM-CFRP system. The present work details an experimental program carried out in order to assess the effect of using three adhesives with distinct mechanical properties on the bond behavior of the NSM-CFRP system, through direct pullout tests (DPT). Thus, the following variables were considered in the present study: (i) the type of adhesive; (ii) the cross section of the laminate; and, (iii) the bond length. The experimental pullout force-slip responses were obtained and digital image correlation (DIC) was used for obtaining additional information about the bond mechanisms developed. In general, two of the three adhesives, with similar mechanical characteristics, provided essentially similar bond behavior, with high level of effectiveness, whereas the third adhesive, which had a much lower elastic modulus than the other two, provided the lowest effectiveness in terms of the investigated parameters.